Comparison of Carotid Intima-Media Thickness (CIMT) and Calcium-Phosphorus (Ca × P) Product Between Hemodialysis (HD) Patients and Continuous Ambulatory Peritoneal Dialysis (CAPD) Patients. - Rosandy, Kharisma Ogit; Winoto, Eden Suryoiman; Samsu, Nur (Clinical and Research Journal in Internal Medicine, 2025)
Background: Cardiovascular disease is the leading cause of death in end-stage renal disease (ESRD). Carotid intima-media thickness (CIMT) and the calcium–phosphate (Ca × P) product are recognised surrogate markers of cardiovascular risk in dialysis recipients. Objective: This study aims to compare CIMT and Ca × P product levels between patients undergoing HD and CAPD. Methods: A cross-sectional study was conducted on 93 dialysis patients (49 HD, 44 CAPD) at Saiful Anwar General Hospital, Indonesia. Participants were over 18 years old, on dialysis for at least three months (HD at least twice weekly), and physically independent. Critically ill and pregnant patients were excluded. The Mann-Whitney U test compared CIMT and Ca × P levels, and Spearman's rank correlation analyzed the relationship between CIMT and Ca × P product Results: Significant differences in CIMT (p=0.0013) and Ca × P product (p<0.0001) were found between the HD and CAPD groups. A positive correlation between CIMT and Ca × P product was observed in HD patients compared to CAPD patients (r = 0.212, p = 0.044), Conclusion: This study revealed that CIMT was higher in HD patients compared to CAPD patients. Furthermore, the Ca × P product was lower in the CAPD group than in the HD group, and a positive correlation existed between CIMT and Ca × P in HD patients.